Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil - De Souza Mondin, Alexandre [UNESP]; Nuvoloni, Felipe Micali [UNESP]; Feres, Reinaldo José Fazzio [UNESP] (Magnolia Press, 2016)
Lorryia (Tydeinae) species are commonly found in surveys of rubber trees (Hevea brasiliensis) in Brazil, although only Lorryia formosa (Cooreman, 1958) has been formally reported from this host. In this study, we described Lorryia parvire- Ticuli sp. nov., L. amazonensis sp. nov., L. fortistriata sp. nov., and L. virga sp. nov., associated with rubber trees from Brazil.
Keywords: Acari; Agroecosystem; Rubber tree; Taxonomy; Tydeinae